Pelaksanaan Pembelajaran Seni Budaya (Teater) di Kelas XI IPS-1 SMA Pertiwi 1 Padang - Sri Amanda Wahyuni Daulay; Harisnal Hadi (SENDRATASIK UNP, 2023)
The purpose of this study describes Cultural Arts Learning (Theater) in class XI social studies 1 SMA Pertiti 1 Padang. This type of research is qualitative research with descriptive methods. This research instrument is the researcher himself and is assisted by supporting instruments such as stationery and cameras. The data in this study used primary data and secondary data. Data collection techniques are carried out by means of literature studies, observations, interviews and documentation. The steps of analyzing data are data collection, data reduction, data presentation and drawing conclusions. The results showed that the learning process was in accordance with the rpp designed but the student score results were still unsatisfactory so that teachers were still remedial to meet the completeness of student scores. Students feel that learning cultural arts is monotonous only by the lecture method and working on student worksheets, so students feel varied when given media such as watching the learning videos given. The implementation of Cultural Arts (Theater) learning using learning media in class XI IPS 1 SMA Pertiwi 1 Padang greatly affects student learning so that supporting will also increase participation, interest in learning and learning outcomes of cultural arts (theater) in class XI IPS 1 even though students have not been able to display the results of modern theater dramas in accordance with established techniques. The implementation of learning can run well and students get grades according to what they do during the learning process.